Art of writing for the theatre : an introduction to script analysis, criticism and playwriting. - Yankee, Luke (London [England] : Bloomsbury Methuen Drama, 2022)
"Writing for the theatre and about theatre requires a diverse set of skills, but whether you're studying theatre or developing your creative craft, this book covers everything you need to know. Providing a practical introduction supplemented with exercises and the testimonies of a host of theatre professionals, it will help you to practise and master the many types of writing encountered in the theatre, including: how to analyze and break down a script; how to write various types of plays, from short plays, plays for one person, to one act and full length dramas; how to critique a play and a theatre production; how to construct and craft essays, cover letters, theatrical resumes, applications, and; how to avoid common grammar and punctuation errors. Filled with practical advice from an award-winning playwright, director, author and college professor, and featuring a range of resources to guide you in the craft and business of theatre writing, The Art of Writing for the Theatre provides everything you need to know to write like a seasoned, theatre professional. Accompanying online resources include playwriting and script analysis worksheets and exercises, an example of a playwriting resume and critical points to consider on playwriting, design, acting, directing and choreography."--
Introduction -- 1. Script Analysis -- 2. Playwriting -- 3. Criticism -- 4. The Interviews: Conversations with Acclaimed Playwrights, Critics, Librettists and Lyricists -- 5. The Brass Tacks: Practical Tools of Writing for the Theatre -- Conclusion -- Appendix: Biographies of Interviewees -- Special Thanks -- Index -- About the Author.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Playwriting; Drama -- Technique; Theatre studies,Writing skills,Creative writing & creative writing guides; Electronic books